Ten Things to Know about K-Pop - Wonseok Lee; Rita Rongyi Lin (Education About Asia, 2026)
How do we understand K-pop? What elements should we look at in grasping K-pop’s rich history? What makes K-pop distinct from other popular music? The authors explore the multifaceted evolution and global phenomenon of K-pop, tracing its origins from early twentieth-century musical adaptations to its current status as a sophisticated multimedia industry. Beginning with historical factors, including the emergence of modern Korean popular music during the colonial period, the impact of the U.S. military, and the 1997 Asian Financial Crisis, this article addresses how these factors catalyzed the genre’s development and forced a strategic shift toward international markets. The authors then question the meaning of K in K-pop by examining how K-pop’s diversification of ethnic, national, and musical boundaries is bound up with its distinct and rigorous trainee system that produces versatile entertainers and transnational identities. Finally, the article highlights the role of highly organized global fandoms, the importance of complex choreography, and the utilization of diverse media platforms to maintain artist-fan connections.
Keywords: K-Pop; Korea; Music